Оцінка відповідності технологічного процесу ТО та ПР моторвагонного рухомого складу у моторвагонному депо “П” вимогам нормативних документів - Колодій, Іван Богданович; Kolodii, Ivan Bohdanovych (Національний університет "Львівська політехніка", 2024)
Метою даної бакалаврської роботи є підвищення надійності, електропоїздів серії ЕР9М, ЕПЛ9Т, дизель-поїздів серії ДР1А, забезпечення встановлених показників безпечності та комфортності перевезень пасажирів. Об’єктом дослідження є система ремонту та технічного обслуговування електропоїздів серії ЕР9М, ЕПЛ9Т, дизель-поїздів серії ДР1А. Предметом дослідження є технологія технічного обслуговування та ремонту електропоїздів серії ЕР9М, ЕПЛ9Т, дизель-поїздів серії ДР1А в умовах моторвагонного депо У бакалаврській роботі проведено оцінку відповідності технологічних процесів технічного обслуговування ТО-2 дизель-поїздів серії ДР1А; технічного обслуговування ТО-2, ТО-3, ТО-4, ТО-5, поточного ремонту ПР-1, ПР-2, ПР-3 електропоїздів серії ЕР9М, ЕПЛ9Т, дизель-поїздів серії ДР1А вимогам нормативної документації. Сформовано перелік невідповідностей організації ТО та ПР електро- та дизель-поїздів нормативним вимогам, запропоновано заходи з усунення невідповідностей шляхом організації ремонтних робіт, удосконалення технології ремонту та впровадження відповідних змін до технологічних процесів. Для досягнення цієї мети у роботі проведено аналіз технологічних процесів технічного обслуговування та поточних ремонтів моторвагонного рухомого складу, наявного обладнання та персоналу в моторвагонному депо. Розглянуто пов’язані питання охорони праці та проведено економічний розрахунок ефективності запропонованих заходів.

The purpose of this bachelor's thesis is to increase the reliability of electric trains of the ER9M, EPL9T series, diesel trains of the DR1A series, ensuring the established indicators of safety and comfort of passenger transportation. The object of the study is the system of repair and maintenance of electric trains of the ER9M, EPL9T series, diesel trains of the DR1A series. The subject of the study is the technology of maintenance and repair of electric trains of the ER9M, EPL9T series, diesel trains of the DR1A series in the conditions of a railcar depot The bachelor's thesis assessed the compliance of technological processes of maintenance of TO-2 diesel trains of the DR1A series; maintenance of TO-2, TO-3, TO-4, TO-5, current repair PR-1, PR-2, PR-3 electric trains of the ER9M, EPL9T, diesel trains of the DR1A series with the requirements of regulatory documentation. A list of inconsistencies in the organization of maintenance and repair of electric and diesel trains with regulatory requirements has been formed, measures have been proposed to eliminate inconsistencies by organizing repair work, improving repair technology and implementing relevant changes to technological processes. To achieve this goal, the work has analyzed the technological processes of maintenance and current repairs of railcar rolling stock, available equipment and personnel in the railcar depot. Related issues of labor protection have been considered and an economic calculation of the effectiveness of the proposed measures has been carried out.
Conformity Assessment of the Maintenance and Running Repair Process of Multiple Unit Rolling Stock at Motor Wagon Depot "P" with the Requirements of Regulatory Documents
Keywords: 6.273.00.02; електропоїзди серії ЕР9М; ЕПЛ9Т; дизель-поїзд серії ДР1А; ремонт; аналіз технологічної та нормативної документації; технологія ремонту; удосконалення; технологічне оснащення; electric trains of the ER9M; EPL9T series; diesel train of the DR1A series; repair; analysis of technological and regulatory documentation; repair technology; improvement; technological equipment